2017
DOI: 10.2460/javma.250.7.770
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation for association between urolithiasis and chronic kidney disease in cats

Abstract: OBJECTIVE To determine whether urolithiasis is associated with chronic kidney disease (CKD) in cats. DESIGN Retrospective case-control study. ANIMALS 126 cats (59 and 67 with and without urolithiasis, respectively). PROCEDURES Medical records from June 2006 to July 2013 were searched to identify cats that underwent abdominal or focal urinary tract ultrasonography and for which serum creatinine concentration and urine specific gravity data were obtained ≤ 14 days before or after the examination. In cats with (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…A positive association between urolithiasis and feline CKD has been reported. 34 This study showed a significantly higher prevalence of CKD among cats with upper urinary tract urolithiasis (33/59 [56%]) than cats without urolithiasis (20/67 [30%]). However, as no causality between urolithiases and CKD was assessed during the study, the authors conclude that it remains unclear whether urolithiasis is a predictive factor for, or a consequence of, CKD.…”
Section: Discussionmentioning
confidence: 70%
“…A positive association between urolithiasis and feline CKD has been reported. 34 This study showed a significantly higher prevalence of CKD among cats with upper urinary tract urolithiasis (33/59 [56%]) than cats without urolithiasis (20/67 [30%]). However, as no causality between urolithiases and CKD was assessed during the study, the authors conclude that it remains unclear whether urolithiasis is a predictive factor for, or a consequence of, CKD.…”
Section: Discussionmentioning
confidence: 70%
“…In the population of cats evaluated, only nine had a kidney failure. The results did not conclude to a positive association between urolithiasis and kidney failure [20].…”
Section: Discussionmentioning
confidence: 57%
“…Urine specific gravity test and urine pH can help to suggest which type of calculus is present and/or detect the presence of urinary tract infections. Calcium oxalate and struvite uroliths are the most commonly identified uroliths in cats [19,20]. Urinary pH is dependent on the type of food in cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal ultrasound was performed by boardcertified radiologists or radiol ogy residents and the diagnosis of nephrolithiasis was made based on previously published criteria. 24 Serum samples of 21 clinically normal cats were obtained in order to establish the normal reference inter val (RI) of total serum magnesium concentrations (mean ± SD, 1.87 ± 0.29 mg/dl; range 1.58-2.16 mg/dl), in accordance with the clinical pathology laboratory/ VTHUSP. Healthy cats were recruited based on normal findings from history and physical examination, as well as in the complete blood count and normal serum biochemical profiles.…”
Section: Methodsmentioning
confidence: 99%